Gut bacteria and cancer - Erdman, Susan E. (Biochim Biophys Acta, 2015)
Microbiota on the mucosal surfaces of the gastrointestinal (GI) tract greatly outnumber the cells in the human body. Effects of antibiotics indicate that GI tract bacteria may be determining the fate of distal cancers. Recent data implicate dysregulated host responses to enteric bacteria leading to cancers in extra-intestinal sites. Together these findings point to novel anti-cancer strategies aimed at promoting GI tract homeostasis.